In-situ segregation of A-site defect (La0.6Sr0.4)0.90Co0.2Fe0.8O3-δ to form a high-performance solid oxide fuel cell cathode material with heterostructure. Issue 4 (15th February 2023) - Bai, Jinghe; Zhou, Defeng; Zhu, Xiaofei; Wang, Ning; Chen, Ruyi; Wang, Bolin; Yan, Wenfu
Abstract: As a potential cathode material for solid oxide fuel cells, the commercial application of La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) has to face the challenges in insufficient oxygen reduction reaction (ORR) activity, segregation of Sr element, and CO2 poisoning. Therefore, the effect of A-site non-stoichiometry on the electrochemical performance of (LS)1-x CFs (x = −0.05, 0, 0.05, 0.10, 0.15) from the aspect of microstructure/elemental surface chemical environment evolution is investigated in this paper. The results show that (LS)0.90 CF has the best ORR activity and the highest electrochemical performance. The excellent electrochemical performance is attributed to the (LS)0.90 CF/Co2 FeO4 /CoFe2 O4 -type heterostructure, formed by in-situ segregation induced by A-site defects, which improves the surface oxygen diffusion coefficient and chemical bulk diffusion coefficient of the cathode. At the same time, the A-site defect can effectively inhibit the segregation of Sr element in (LS)0.90 CF, thereby improving the tolerance of CO2 . At 800 °C, the area-specific resistance (ASR) of (LS)0.90 CF (0.023 Ω cm 2 ) is 66.7% lower than that of LSCF (0.069 Ω cm 2 ), and the peak power density (1.57 Wcm −2 ) is 1.8 times higher than that of LSCF (0.87 Wcm −2 ). Therefore, perovskite A-site defect-induced B-site segregation to form heterostructures provides an effective strategy for the preparation of high-performance cathode materials.